2021
DOI: 10.1186/s12879-021-06709-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in acute pancreatitis complicated with multidrug-resistant Klebsiella pneumoniae infection

Abstract: Background Multidrug-resistant (MDR) Klebsiella pneumoniae infections, from pancreatic infections to bloodstream infections, influence the mortality of patients with acute pancreatitis (AP) on the condition of limited antibiotic choices. The aim of this study was to investigate the predictor of mortality among AP patients complicated with MDR-K. pneumoniae infections. Methods Seventy-one AP patients who occurred MDR-K. pneumoniae infections from Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Similar to previous research, our study showed that CRO are highly resistant to most common antibiotics, which may be attributed to the clinical use of wholly prophylactic antibiotic prescription [ 17 , 31 ]. The vast majority of CAP patients received antibiotics before the IPN intervention because of suspected infections with possible manifestations.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to previous research, our study showed that CRO are highly resistant to most common antibiotics, which may be attributed to the clinical use of wholly prophylactic antibiotic prescription [ 17 , 31 ]. The vast majority of CAP patients received antibiotics before the IPN intervention because of suspected infections with possible manifestations.…”
Section: Discussionsupporting
confidence: 88%
“…In line with Li et al., hyperlipidaemia was the primary aetiology in the IPN patients, but it was interesting that the biliary aetiology was more frequent in patients within the MDR-GNB bacteraemia group than the contrast group, thus suggesting that MDR-GNB bacteraemia could be secondary to bacterial translocation through the gut ( Flint and Windsor, 2003 ; Li et al., 2020 ; Yang and McNabb-Baltar, 2020 ). In addition, these invasive treatments may result in bacteraemia, especially MDR-GNB bacteraemia ( Wu et al., 2021b ). In our study, there were also 12 of 24 patients diagnosed with bacteraemia during the post-intervention (≤5 days), which may be possibly related to translocation secondary to intervention and needs to be validated in the larger sample size study.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-positive bacterial or fungal infections were defined as the presence of concomitant infections ( Wu et al., 2022b ). MDR- GNB is defined as strains not sensitive to three or more categories of antibiotics ( Wu et al., 2021b ). Combination antibiotic therapy was defined as a regimen with at least two categories of antibiotics based on the condition of patients and approved by infectious disease specialists.…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey conducted in 41 countries by the Central Asian and the European Surveillance of Antimicrobial Resistance network ( 11 ) revealed that >50% of the isolates recovered from patients (predominantly in Southern and Eastern Europe) were resistant to third-generation cephalosporins and >25% were resistant to carbapenems. Moreover, mortality rates caused by MDR K. pneumoniae have been reported to be as high as 50% or higher in clinical settings ( 12 , 13 ). This is further exacerbated by new emerging clones, such as sequence types 101 (ST101), ST307, and ST147, which have acquired virulence factors and antimicrobial resistance (AMR) genes, contributing to their success as persistent nosocomial infections ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%